Do problema das identidades na pós-modernidade - Flores, Fabiano Rocha (2011)
We realize that the passage of Modernity to Postmodernity worked somewhat problematic for the identities. Specifically about what of the identity is problematic for this new condition is that we dedicate here. To this end, we articulated theories about identity, mediazation and psychoanalysis to propose our understanding of the formation of identities in postmodernity. This link leads to the media as a hegemonic cultural institution and, therefore, proposing the main parameters for the formation of identities in nowadays, what causes it resides our empirical analysis. We analyzed semiotically four sitcoms in search of a sample of these identity parameters from which the identities are forming. It is in possession of such parameters that we reach an answer to our initial question: that it would be to transfer responsibility for conduction of the process of symbolization of identities choices of social institutions to the individual isolate, precisely the difficulty of some in perform this function, the problem of identities in Postmodernity.